Moral and Spiritual Self-Improvement of Russian Youth in the Context of Religious and Cultural Awareness - Gabdulbarovna Mukhametzyanova, Flera (2021)
In the research the relation to a symbol of the icon of Kazan Mother of God is considered through the structure of identity of group of modern Cristian youth. Today the religiousness, religious belief is a psychological phenomenon focusing the person on a way of moral and spiritual self-improvement. The relation of citizens to Russian Cristian Church remains contradictory, especially at youth. In this regard the research of the relation to a unique historical and cultural and spiritual symbol of the Kazan icon of the Mother of God is perspective. It is one of the brightest and deepest Cristian symbols it content. History of the Kazan icon of the Mother of God is inseparably linked with the history of Russia. The purpose of this article is to present the results of the research aimed in the identification of the relation to a symbol of the Kazan icon of the Mother of God of modern Cristian youth in the context of interrelation of its confessional identity and religious and cultural awareness. Results of an empirical research allows to establish that, despite growth of religious interest in a symbol of an icon of Kazan Mother of God at young people the low level of knowledge, not formation of ideas of the historic facts connected with this icon is observed. The image of an icon and its historical context have the invaluable potential for spiritual and moral education of the Russian youth.